Respuesta :
Answer:
r(q(-4)) = -10
Step-by-step explanation:
q(x) = -x - 2
r(x) = -2x^2 -2
r(q(-4))
First find q(-4)
Let x=-4
q(-4) = -(-4) - 2
q(-4) = +4 -2 = 2
q(-4) =2
We substitute this value in for x in r(x)
r(2) = -2(2)^2 -2
= -2 (4) -2
= -8 -2
= -10
For this case we have the following functions:
[tex]q (x) = - x-2\\r (x) = - 2x ^ 2-2[/tex]
We must find [tex]r (q (x))[/tex]. So:
We substitute [tex]q (x)[/tex]in [tex]r (x).[/tex]
[tex]r (q (x)) = - 2 (-x-2) ^ 2-2[/tex]
Now we substitute[tex]x = -4[/tex]
[tex]r (q (-4)) = - 2 (- (- 4) -2) ^ 2-2\\r (q (-4)) = - 2 (+ 4-2) ^ 2-2\\r (q (-4)) = - 2 (2) ^ 2-2\\r (q (-4)) = - 2 (4) -2\\r (q (-4)) = - 8-2\\r (q (-4)) = - 10[/tex]
Answer:
[tex]r (q (-4)) = - 10[/tex]